Recovery Of Copper From E-Waste Via Hydrometallurgy Method - Rosli, Nur Ain (Universiti Sains Malaysia, 2022)
E-waste production is increasing by time as the demand of society in electronics grows year by year. Since, e-waste contain both hazardous metals and precious metals such as copper, recovery of the metals are necessary to minimize environmental and to gain benefits from monetary metals. In this work, the pysico-chemical characteristic of Waste Printed Circuit Board (WPCBs)is determined via XRF, XRD and SEM analysis and to compare the recovery of copper with three different leaching parameters, temperature, rate of oxidant addition and effect of ultrasonic pre-treatment. In XRF analysis, the major composition in the e-waste were SiO2, Ca followed by CuO element. This result was supported by XRD test where the most significant phase with high peak that exist in the sample is copper along with SiO2. SEM analysis was also done to analyse the impact of ultrasonic pre-treatment which show high copper separation from unwanted particles such as ceramic and plastic. For SEM analysis, the most significant condition was sample that treated with ultrasonic. The fixed parameters in leaching are S/L ratio (1:10), sulphuric acid concentration (1.5 M), volume of sulphuric acid (100 ml), size of leaching sample (below than 200 µm) and stirring rate (300 rpm). Meanwhile, the manipulated parameter used to achieve high leaching rate are temperature (30°C and 60°C), rate of oxidant addition (20 ml/hr and 60 ml/hr) and effect of ultrasonic pre-treatment. The optimum condition for high recovery rate of copper, 64.36%, were addition of 5% hydrogen peroxide at rate 20ml/hr at 60°C.